EARLY-STAGE NASOPHARYNGEAL CARCINOMA: A CASE REPORT - Izry Naomi Tobing (TALENTA PUBLISHER, 2019)
Introduction: NPC is a highly prevalent malignant disease in endemic regions such as Southeast Asia. Until now, most NPC patients have bben diagnosed in advanced stages. Early-stage NPC is difficult to diagnose clinically. The study present a case of early-stage NPC with the symptoms of progressive ringing in the ear. Case report: A 56 years old male presented with two months history of progressive unilateral ringing in the ear. The patient had been previously diagnosed and treated for Eustachian tube dysfunction. Endoscopic examination of nasopharynx showed a mass in the left fossae of Rosenmüller. CT scan depicted soft tissue thickening on the left side of the nasopharynx. Nasopharyngeal histopathology revealed a non-keratinizing squamous cell carcinoma. The patient underwent radiotherapy and up to date, no complaints have been encountered. Conclusion: Early detection of NPC will improve patient’s prognosis.